Dietary vitamins, carotenoids and their sources in relation to age-related macular degeneration risk in China: a population-based case–control study. Issue 10 (28th May 2023) - Jiang, Hong; Wang, Lina; Li, Juan; Fan, Yahui; Li, Zhaofang; Ma, Mei; Liu, Sijiao; Li, Baoyu; Shi, Jia; Li, Chao; Mi, Baibing; Chen, Fangyao; et al.
Abstract: Mechanistic studies have suggested that antioxidants have beneficial effects on age-related macular degeneration (AMD). This study aimed to investigate the association between the types and sources of dietary vitamin and carotenoid intakes and AMD risk in China. A matched case–control study of 260 AMD cases and 260 matched controls was performed. The participants were interviewed for dietary information and potential confounders, and comprehensive ophthalmic examinations were performed. Conditional logistic models were used to estimate the odds ratio (OR) and 95 % confidence interval (CI) of specific vitamins and carotenoids and their main sources. When comparing the extreme quartiles, the ORs (95 % CI) were 0·30 (0·10, 0·88) for lutein and 0·28 (0·11, 0·74) for β -cryptoxanthin. The associations for other dietary vitamin and carotenoid intakes were generally weaker and non-significant. Higher intakes of spinach and egg, which are important sources of lutein, were associated with a reduced odds of AMD. ORs (95% CIs) comparing extreme categories were 0·42 (0·20, 0·88) for spinach and 0·52 (95% CI: 0·27, 0·98) for egg. Participants who were in the highest category of both egg intake and spinach intake had a much greater reduced odds of having AMD (OR: 0·23; 95% CI: 0·08, 0·71) than those in the lowest category of egg intake and spinach intake. In conclusion, a higher intake of lutein and lutein-rich foods was associated with a significantly decreased odds of AMD. These findings provide further evidence of the benefits of lutein and lutein-rich foods in the prevention of AMD.